EVALUASI SISTEM ZONASI TERHADAP DAYA SERAP PESERTA DIDIK - Andika Pramaisella (Jurnal Tata Kelola Pendidikan, 2021)
This study entitled the evaluation of the zoning system on the absorption capacity of SMA Negeri 1 Cibadak. The general objective of this study is to determine the extent of the success of the zoning system implemented by the government in absorbing students in SMA Negeri 1 Cibadak. This study uses a descriptive method using a qualitative approach. Data collection using the interview method. The population in this study were the principal, the head of PPDB, and 2 teachers at SMA Negeri 1 Cibadak. The data were analyzed by data reduction and drawing conclusions in narrative form. The results showed that the evaluation of the zoning system began with the acceptance of new students using the provisions set by Education and Culture, 50% of students from the zoning system, 25% of the achievement pathway, 15% of the affirmation pathway, and 5% of the parent transfer path. The quality of the school is very decisive for the results of this program, the quality of the teachers also determines the final outcome of the students who attend SMA Negeri 1 Cibadak. This is the spirit of the achievement of students and schools. For this reason, SMA Negeri 1 Cibadak feels that it can accept all students in the implementation of new students for the 2020-2021 school year quota of 36 people times 12 classes